IMPLEMENTASI AEC DALAM PENINGKATAN JARINGAN PRODUKSI REGIONAL ASEAN: STUDI KASUS INDUSTRI OTOMOTIF - Herdianto, Enggar Furi (Dauliyah Journal of Islamic and International Affairs, 2016)
ASEAN Economic Community (AEC) is one of bog changes that is being done by ASEAN on its attempt in integrating the region. One of this community vision is to bring ASEAN on becoming one regional production network, where ASEAN would not be seen as separate entity, instead ASEAN would be seen as one integrated area of investment. In this paper, automotive industry is chosen because of its history in the region as one of sector that has been developed for a long time and always have full support from the domestic government. This paper will try to analyze the effectiveness of AEC implementation in developing regional production network of automotive industry, and how far each of domestic government are willing to push this integration effort.